Capture-recapture methods to size alcohol related problems in a population - Corrao, G. (BMJ Group, 2000)
STUDY OBJECTIVE—To investigate the utility of capture-recapture methods to estimate prevalence of subjects with alcohol related disorders using multiple incomplete lists. DESIGN—This was a cross sectional study of alcohol related disorders in a large community. SETTING—During 1997 identified cases with known alcohol related disorders were independently flagged by four sources (self help volunteering groups; psychiatric ambulatory; public alcohology service; hospital discharges). PATIENTS—381 records were flagged, corresponding to 349 individual cases from a target population resident in a northern Italy area. MAIN RESULTS—The two sample capture-recapture estimates were clearly biased because of dependencies among sources. Estimates based on log-linear models showed prevalent counts ranged from 2297 (95% confidence intervals: 1524, 3794) to 2523 (95% confidence intervals: 1623,( )4627) after adjustment for dependence among sources only or also for heterogeneity in catchability among age categories (< 50 and ⩾ 50 years), respectively. CONCLUSIONS—The study suggests that capture-recapture is an appropriate approach for estimating prevalence of subjects with alcohol related problems who seek or need treatment and assistance when different lists of alcoholics can be obtained from different types of agencies involved with problematic use of alcohol. Critical factors are the complexity in case definition and the analysis of heterogeneity among people. Accurate estimates are needed to plan and evaluate public health interventions.   Keywords: alcohol related problems; capture-recapture; log-linear models